산수화에서의 소요(逍遙)에 담긴 노마드감성에 관한 연구 - 강민희; Min Hee Kang; 조택연; 교신저자; Taig Youn Cho (기초조형학연구, 2015)
산수화는 중국에서 발생한 대표적인 공간표현 및 인식체계이다. 대상으로서의 산(山)과 수(水)를 넘어서, 그것이 둘러싼공간의 분위기를 화폭에 담아낸다. 이는 공간에 대한 호감이 시각적 대상으로 표현된 것이다. 이러한 공간호감의 표현형은 감상자로 하여금 그 공간을 인지하고, 가상적으로 체험하는 소요(逍遙)를 경험하게 만든다. 그림 속에서 ‘한가롭게 거닐음’으로써 정신적인 자유를 얻는 ‘소요유(逍遙遊)’는 동양미학적 가치로 해석되며 그 예술적 가치를 인정받아 왔다. 본연구는 진화심리학을 도구로 산수화에서의 소요에 담긴 노마드(nomad)감성의 유형을 분류하는데 그 목적이 있다. 연구자는 소요가 노마드감성으로부터 작용하며, 홍적세로부터 오랜 시간에 걸쳐 생존을 위한 이동에서 갖게 된 마음이라고 보았다. 화폭에서 경험하는 소요는 감상자의 심상(mental imagery)처리를 통해 작용하기 때문에 실제와 똑같은 경험이 가능하다. 그러므로 인간이 실제 공간을 이해, 탐색할 때의 진화심리학적 선호 매트릭스를 근거로 노마드감성에 대한 연구를 진행하였다. 북송대 산수화를 선도한 대가로 칭송받으며, 섬세한 필체와 표현으로 산수화에서의 소요를 가장 잘 드러낸 3인인 곽희, 범관 그리고 이성의 대표작에서 공통적으로 나타나는 노마드감성 요소를 진화심리학자 카플란(Kaplan)의 선호 매트릭스에 대응시켜 보았다. 그 결과로 산수화에서 감상자가 소요하게 만드는 요소인 ‘시선의 유인’,‘시선의 유도’, ‘시선의 머묾’ 그리고 ‘시선의 연결’의 총 4가지 노마드감성 유형을 분류하였고, 이를 통하여 세 대표작에 담긴 소요를 노마드감성으로써 해석할 수 있었다. 또한, 이러한 노마드감성은 이동에 대한 인간의 보편적 선호로, 공간에서 즐거움과 흥미라는 유희를 추구하기 위한 일련의 과정이 됨을 알 수 있었다. 본 연구에서는 그동안 동양미학의 환경 내에서 해석되어 온 산수화에서의 소요를 진화심리학적 틀에서 접근해 봄으로써, 산수화에서의 소요를 노마드감성을 통한 소요에 대한 호감으로 이해할 수 있었다. 진화심리학적 지식환경 내에서도 공감 받을 수 있는 보편적 가치로서의 소요에 대한 접근이 노마드감성의 요소를 적용한 소요의 유희적 공간 디자인에 새로운 기점이 될 것으로 기대한다. Landscape paintings are typical spatial recognition and expression system introduced in China. Canvas describes not only the objects such as mountains and waters but the air of surrounding space. This means that likability of space is visibly expressed on canvas. This kind of expression of space-likability enables appreciators to understand and feel the image of the space. As such, ``free and easy wandering`` enables appreciators to freely take a stroll inside the painting which is eastern aesthetic value that gives psychological freedom. This study confirms that emotional nomad isinherent in free and easy wandering of landscape paintings. Thus, the purpose of this study is to use evolutionary psychology as the tool of emotional nomad classification. The researcher regarded free and easy wandering that appears in landscape painting as a work from emotional nomad. And it had become as a mind which is movement-likability gotten from long-term movement for survival since the age of Pleistocene. Free and easy wandering on canvas is the result of mental imagery of spatial experience of appreciator with emotional nomad. Thus, the study uses Kaplans preference matrix as basis to understand and explore the real space. Result from comparing common elements of emotional nomad those appear in paintings of 3 representative north Song Dynasty artist and Kaplans preference matrix. The researcher classified 4 elements of free and easy wandering, as ‘attract of attention’, ‘lead of attention’, ‘stay of attention’ and ‘link of attention’. This emotional nomad is the universal preference of movement, and is the series of process to persue amusement such as enjoyment and interest. Free and easy wandering was usually dealt in the eastern aesthetics, however, this study uses evolutionary psychology to understand emotional nomad of likability of perspective shift. Understanding emotional nomad in a new knowledge environment will be the tool to understand the value of landscape paintings in a new way. The researcher expect that such a approach which could gain sympathy in psychological environment as a universal value of free and easy wandering, becoming a new point of designing an free and easy wandering and amusing space applying 4 elements of emotional nomad.